Application of CSPC composite shear wall equipped with tension-and-compression damper in multi-storey structures. (April 2022) - Hosseinlou, Farhad; Labibzadeh, Mojtaba
Abstract: The purpose of this study is to investigate the performance and application of concrete composite shear walls with corrugated steel sheet equipped with damper system in a variety of real structures of 4, 8 and 15 storey under seismic load. In the studied structures, the seismic load-bearing system includes the dual system of special moment- resisting frame in combination with the mentioned concrete composite shear wall. To achieve the objectives of the present study, the replaceable vertically corrugated steel plate-concrete (CSPC) composite shear wall (i.e. NEW_V) and the replaceable horizontally CSPC composite shear wall (i.e. NEW_H) equipped with replaceable dampers are simulated utilizing ABAQUS software. In order to gain the sections and profiles of the dual system employed in ABAQUS software, ETABS software is applied for modeling and designing in accordance with the required standards. First, to ensure the conformity of the numerical model with the laboratory model of the mentioned shear walls, validation is accomplished. Criteria such as displacement, stiffness, shear capacity and energy dissipation are compared for validation. Based on the validation results, the outputs of the numerical models of the present study are in good agreement with the laboratory results. After performing the necessary simulation and modeling, the proposed scheme is implemented on the proposed structures. It can be said that structures equipped with damper had better performance (between 25% and 35%) than structures without damper (for both NEW_V and NEW_V specimens). The reason is the creation of less base shear in structures equipped with damper under seismic force. Thus, these structures have good energy absorption and ductility. Also, the stiffness of these structures is not significantly reduced.